Impacts of Water Runoff during Heavy Rainfall in the HouayKhan Catchment, XiengNgeun District - Thongmany, Sayasone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to analyze the relationship between rainfall, streamflow, and changes in physical (SSL, Turbidity, Temperature) and biological (E. coli) water quality in XaingNgeun District, Luang Prabang Province. Data collection was conducted using an automated monitoring system, including a CR800 Datalogger and an ISCO automated water sampler, to monitor three distinct conditions: low intensity rainfall (20 mm/h), moderate rain (40-80 mm/h), and heavy rain (150 mm/h). The results indicate that rainfall is the primary driver significantly controlling water quality fluctuations (p < 0.0001). During heavy rain events, streamflow increased rapidly to 80 m³/s, causing turbidity to exceed 3,500 NTU and Suspended Sediment Load (SSL) to peak at 60 g/l due to intense soil erosion in steep terrain. Biologically, E. coli contamination increased substantially, with mean concentrations exceeding 30,000 MPN/100 ml and occasionally reaching 100,000 MPN/100 ml during the " effect " period. Additionally, rainfall events triggered a sudden decrease in water temperature and reduced Electrical Conductivity (EC) due to the dilution effect of rainwater. The study confirms that suspended sediments act as a major carrier for pathogens entering the waterway. These findings highlight the public health risks for communities relying on surface water during the rainy season. This data provides a crucial foundation for sustainable water and land management planning, flash flood forecasting, the design of water treatment systems, and the development of public health warning systems for downstream communities in the Nam Khan stream.